Removing Singularities of the Generalized Logistic Equation on Time Scales - Wells, Amy; Williams, Tristan (My University, 2011)
A time scale is a non-empty closed subset of the real numbers. This study looks at the generalized logistic equations on time scales.
Color poster with text and diagrams.
Keywords: Singularities (Mathematics); Equations--Numerical solutions; Numbers, Real; Posters